A kind of transfer adhesive resin and preparation method thereof

By synthesizing and reacting specific polyester polyols, isocyanate and acrylate monomers, oligomer resins are prepared, which solves the problem of insufficient toughness and wear resistance of existing UV transfer glues, and achieves excellent curing speed and resistance. Abrasiveness and toughness.

CN116003733BActive Publication Date: 2025-02-07NANXIONG YALTON CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211674449.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-02-07
Estimated Expiration
2042-12-26

AI Technical Summary

Technical Problem

The existing UV transfer glue has the disadvantages of being brittle after curing, insufficient toughness, and no yellowing, and poor practical application effect.

Method used

By synthesizing saturated polyester polyol E1 with a molecular weight of 600 to 1200 and polyester polyol E2 with a molecular weight of 500 to 1000, it is reacted with isocyanate and acrylate monomer to control the ratio and reaction conditions of the polyester polyol to prepare Oligomer resin.

Benefits of technology

The toughness and wear resistance of the transfer glue are significantly improved, the curing energy is below 800w/cm2, the wear resistance is >500 times, the hardness is above F, and the bending resistance is above 3mm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004017574730000011
    Figure BDA0004017574730000011
  • Figure BDA0004017574730000031
    Figure BDA0004017574730000031
  • Figure BDA0004017574730000061
    Figure BDA0004017574730000061
Patent Text Reader

Abstract

The present invention provides a transfer adhesive resin and a preparation method thereof. The preparation method of the transfer adhesive resin provided by the present invention comprises: a) mixing an alcohol monomer, a dibasic acid substance and an esterification catalyst to obtain a saturated polyester polyol E1; the dibasic acid substance is at least one of a dibasic acid, a dimer acid and a dibasic acid anhydride; b) mixing an alcohol monomer, a caprolactone monomer and a ring-opening catalyst to obtain a polyester polyol E2; the alcohol monomer comprises a cyclic alcohol monomer; c) mixing the materials to obtain an intermediate reactant; the material comprises the following components in parts by weight: 10 to 20 parts of saturated polyester polyol E1; 15 to 30 parts of polyester polyol E2; 10 to 20 parts of isocyanate; 0.1 to 1 part of catalyst; 0.1 to 1 part of polymerization inhibitor; d) mixing the intermediate reactant with an acrylate monomer to obtain a transfer adhesive resin. The transfer adhesive resin can effectively improve toughness and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesives, and in particular to a transfer adhesive resin and a preparation method thereof. Background Art

[0002] UV transfer adhesive is mainly used for the decoration of the outer shell of consumer electronic products, including the transfer of surface textures of outer shells such as mobile phones, computers, refrigerators, and car decorative parts. By utilizing the non-stick properties of UV transfer adhesive and metal, various brushed patterns are transferred from the composite sheet to another substrate through the UV transfer adhesive process, thereby creating light columns, bright surface effect patterns, gradients and other effects. Especially now that many mobile phone covers use 3D glass, UV transfer adhesive is even more needed, so UV transfer adhesive is a new breakthrough in mobile phone covers. Currently, the UV transfer adhesive on the market has the disadvantages of being brittle after curing, lacking toughness, and not yellowing, and the actual application effect is not good. Summary of the invention

[0003] In view of this, the present invention provides a transfer adhesive resin and a preparation method thereof. The transfer adhesive resin provided by the present invention can effectively improve toughness and wear resistance.

[0004] The present invention provides a method for preparing a transfer adhesive resin, comprising the following steps:

[0005] a) mixing an alcohol monomer, a dibasic acid substance and an esterification catalyst to react to obtain a saturated polyester polyol E1;

[0006] The dibasic acid substance is at least one of a dibasic acid, a dimer acid and a dibasic acid anhydride;

[0007] b) mixing an alcohol monomer, a caprolactone monomer and a ring-opening catalyst to react to obtain a polyester polyol E2;

[0008] The alcohol monomer comprises a ring-carrying alcohol monomer;

[0009] c) mixing and reacting the materials to obtain an intermediate reactant;

[0010] The material comprises the following components in parts by weight:

[0011]

[0012]

[0013] d) mixing the intermediate reactant with an acrylate monomer to obtain a transfer adhesive resin;

[0014] There is no order restriction for step a) and step b).

[0015] Preferably, in step a), the dibasic acid substance is at least one of adipic acid, succinic acid, dimer acid, phthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and 1,4-cyclohexanedicarboxylic acid.

[0016] Preferably, in step a), the alcohol monomer is at least one of 1,4-cyclohexanedimethanol, methylpropanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, trimethylolpropane and pentaerythritol.

[0017] Preferably, in step a), the reaction temperature is 180-230°C.

[0018] Preferably, in step b), the alcohol monomer is at least one of 1,4-cyclohexanedimethanol, 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol, and contains 1,4-cyclohexanedimethanol.

[0019] Preferably, in step b), the reaction temperature is 110-130°C.

[0020] Preferably, in step d), the acrylate monomer is at least one of pentaerythritol diacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate.

[0021] Preferably, in step c), the reaction temperature is 40-60°C;

[0022] In step d), the reaction temperature is 70-90°C.

[0023] Preferably, in step a), the amount of each material is:

[0024] 40 to 65 parts by weight of alcohol monomer;

[0025] 30 to 50 parts by weight of dibasic acid;

[0026] 0.1 to 1 parts by weight of esterification catalyst;

[0027] In step b), the amount of each material is:

[0028] 20 to 40 parts by weight of alcohol monomer;

[0029] 30 to 65 parts by weight of caprolactone monomer;

[0030] 0.1 to 1 part by mass of a ring-opening catalyst;

[0031] In step c):

[0032] The isocyanate is at least one of TMDI, hydrogenated MDI, IPDI and XDI;

[0033] The catalyst is an organic bismuth catalyst;

[0034] The polymerization inhibitor is at least one of p-hydroxyanisole, hydroquinone and 2,6-di-tert-butylphenol.

[0035] The present invention also provides a transfer adhesive resin prepared by the preparation method described in the above technical solution.

[0036] The preparation method provided by the present invention first prepares two different polyester polyols E1 and E2 respectively, controls the molecular weights of the two polyester polyols, and then reacts the two polyester polyols with isocyanate and acrylate monomers. During the process, the ratio of the two polyester polyols and the ratio between the two polyester polyols and other reactants and the reaction conditions are controlled to obtain an oligomer resin that can be used for transfer adhesives. The toughness and wear resistance of the resin can be effectively improved to meet the special needs of the transfer adhesive market.

[0037] The test results show that the transfer adhesive resin obtained by the present invention can make the curing energy of the transfer adhesive be 800w / cm 2 Below, wear resistance RCA>500 times, hardness above F, bending resistance value above 3mm, showing excellent curing speed, wear resistance and toughness. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a transfer adhesive resin, comprising the following steps:

[0039] a) mixing an alcohol monomer, a dibasic acid substance and an esterification catalyst to react to obtain a saturated polyester polyol E1;

[0040] The dibasic acid substance is at least one of a dibasic acid, a dimer acid and a dibasic acid anhydride;

[0041] b) mixing an alcohol monomer, a caprolactone monomer and a ring-opening catalyst to react to obtain a polyester polyol E2;

[0042] The alcohol monomer comprises a ring-bearing alcohol monomer;

[0043] c) mixing and reacting the materials to obtain an intermediate reactant;

[0044] The material comprises the following components in parts by weight:

[0045]

[0046] d) mixing the intermediate reactant with an acrylate monomer to obtain a transfer adhesive resin;

[0047] There is no order restriction for step a) and step b).

[0048] The present invention synthesizes a saturated polyester polyol E1 with a molecular weight of 600 to 1200 by a high temperature melting method, and uses a small molecular alcohol as an initiator to open a cyclohexyl lactone monomer to synthesize a polyester polyol E2 with a molecular weight of 500 to 1000, and reacts the self-designed and synthesized polyester polyols E1 and E2 with isocyanate to prepare a prepolymer, and finally reacts the modified acrylate monomer with the prepolymer to obtain an oligomer resin. The use of the above oligomer resin can effectively improve the toughness and wear resistance of the resin and meet the special needs of the transfer adhesive market.

[0049] Regarding step a) :

[0050] a) mixing an alcohol monomer, a dibasic acid substance and an esterification catalyst to react to obtain a saturated polyester polyol E1.

[0051] In the present invention, the alcohol monomer is a small molecule alcohol, preferably at least one of 1,4-cyclohexanedimethanol, methylpropanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, trimethylolpropane and pentaerythritol.

[0052] In the present invention, the dibasic acid substance is at least one of dibasic acid, dimer acid and dibasic acid anhydride; preferably at least one of adipic acid, succinic acid, dimer acid, phthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride and 1,4-cyclohexanedicarboxylic acid.

[0053] In some embodiments of the present invention, the alcohol monomer and the dibasic acid substance are matched as follows: the alcohol monomer is 3-methyl-1,5-pentanediol and 1,4-cyclohexanedimethanol, and the dibasic acid substance is dimer acid; or the alcohol monomer is 3-methyl-1,5-pentanediol, and the dibasic acid substance is adipic acid and 1,4-cyclohexanedicarboxylic acid; or the alcohol monomer is 2,4-diethyl-1,5-pentanediol, and the dibasic acid substance is dimer acid and methylhexahydrophthalic anhydride.

[0054] In the present invention, the esterification catalyst is preferably tetrabutyl titanate and / or isopropyl titanate.

[0055] In the present invention, in step a), the amount of each material is preferably as follows:

[0056] 40 to 65 parts by weight of alcohol monomer;

[0057] 30 to 50 parts by weight of dibasic acid;

[0058] 0.1 to 1 part by mass of esterification catalyst

[0059] The amount of the alcohol monomer can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, and 65 parts. The amount of the dibasic acid can be 30 parts, 35 parts, 40 parts, 45 parts, and 50 parts. The amount of the esterification catalyst can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, and 1.0 parts.

[0060] In the present invention, the reaction is preferably carried out under a protective atmosphere. The present invention has no particular limitation on the type of gas providing the protective atmosphere, and any conventional protective gas known to those skilled in the art may be used, such as nitrogen or argon.

[0061] In the present invention, the reaction temperature is preferably 180-230°C, specifically 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C. In the present invention, the reaction time is preferably 6-12h, specifically 6h, 7h, 8h, 9h, 10h, 11h, 12h. After 6-12h of reaction, start recording the water output and testing the acid value. When the acid value is less than 10mgKOH / g, remove the remaining water by vacuum until the acid value is less than 1mgKOH / g, terminate the reaction, and obtain saturated polyester polyol E1.

[0062] In step a) of the present invention, a saturated polyester polyol E1 is synthesized by a high temperature melting method. The obtained saturated polyester polyol E1 has a number average molecular weight of 600 to 1200, contains 4 to 8 ester bonds on the main chain, has at least one cyclic structure, has ≥2 terminal hydroxyl groups, and contains a C2 to 4 alkyl group on the side chain.

[0063] Regarding step b) :

[0064] b) mixing an alcohol monomer, a caprolactone monomer and a ring-opening catalyst to react to obtain a polyester polyol E2.

[0065] In the present invention, the alcohol monomers include cyclic alcohol monomers, which can be divided into two situations: (1) all the alcohol monomers are cyclic alcohol monomers; (2) the alcohol monomers contain both cyclic alcohol monomers and non-cyclic alcohol monomers; wherein the cyclic alcohol monomers refer to alcohol monomers with a cyclic structure. When it is the second situation, that is, the alcohol monomers include cyclic alcohol monomers and non-cyclic alcohol monomers, wherein the mass ratio of the cyclic alcohol monomers in the total amount of alcohol monomers is preferably 30% to 60%, specifically 30%, 35%, 40%, 45%, 50%, 55%, 60%. In the present invention, the alcohol monomer is preferably at least one of 1,4-cyclohexanedimethanol, 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol, and contains 1,4-cyclohexanedimethanol.

[0066] In the present invention, the caprolactone monomer is also called ε-caprolactone monomer, and its source is not particularly limited, and it can be a commercial product.

[0067] In the present invention, the ring-opening catalyst is preferably at least one of phosphoric acid and triphenylphosphine.

[0068] In the present invention, in step b), the amount of each material is preferably as follows:

[0069] 20 to 40 parts by weight of alcohol monomer;

[0070] 30 to 65 parts by weight of caprolactone monomer;

[0071] 0.1 to 1 part by mass of the ring-opening catalyst.

[0072] The amount of the alcohol monomer can be 20 parts, 25 parts, 30 parts, 35 parts, and 40 parts. The amount of the caprolactone monomer can be 30 parts, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, and 65 parts. The amount of the ring-opening catalyst can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, and 1.0 parts.

[0073] In the present invention, the reaction is preferably carried out under a protective atmosphere. The present invention has no particular limitation on the type of gas providing the protective atmosphere, and any conventional protective gas known to those skilled in the art may be used, such as nitrogen or argon.

[0074] In the present invention, the reaction temperature is preferably 110-130° C., specifically 110° C., 115° C., 120° C., 125° C., 130° C. In the present invention, the reaction time is preferably 6-10 h, specifically 6 h, 7 h, 8 h, 9 h, 10 h. After the above reaction, polyester polyol E2 is obtained.

[0075] In step b) of the present invention, a small molecule alcohol is used as an initiator to synthesize a polyester polyol E2 from a cyclohexyl lactone monomer. The obtained polyester polyol E2 has a number average molecular weight of 500 to 1000, contains 2 to 8 repeated (CH2)6 structural units on the main chain, and contains cyclic structures at both ends of the chain.

[0076] The present invention has no particular limitation on the order of the above step a) and step b).

[0077] Regarding step c) :

[0078] c) Mixing and reacting the materials to obtain an intermediate reactant.

[0079] In the present invention, the material includes the following components in parts by weight:

[0080]

[0081] in:

[0082] The specific usage of the saturated polyester polyol E1 can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, or 20 parts.

[0083] The specific usage of the polyester polyol E2 can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, and 30 parts.

[0084] The isocyanate is preferably at least one of TMDI, hydrogenated MDI, IPDI and XDI. The amount of the isocyanate can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts.

[0085] The catalyst is preferably an organic bismuth catalyst, more preferably an organic bismuth catalyst MC-710. The amount of the catalyst used can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, or 1.0 part.

[0086] The polymerization inhibitor is preferably at least one of p-hydroxyanisole, hydroquinone and 2,6-di-tert-butylphenol. The dosage of the polymerization inhibitor can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part or 1.0 part.

[0087] In the present invention, the reaction temperature is preferably 40-60° C., specifically 40° C., 45° C., 50° C., 55° C., 60° C. The reaction time is preferably 2-4 hours, specifically 2 hours, 3 hours, 4 hours. When the reaction is carried out to the NCO% close to the theoretical value, an intermediate reactant is obtained, and the next step is started.

[0088] Regarding step d) :

[0089] d) mixing the intermediate reactant with an acrylate monomer to obtain a transfer adhesive resin.

[0090] In the present invention, the acrylate monomer is preferably at least one of pentaerythritol diacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate. In the present invention, based on 10 to 20 parts of saturated polyester polyol E1 in step c), the amount of the acrylate monomer is preferably 30 to 60 parts, specifically 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60 parts.

[0091] In the present invention, the reaction temperature is preferably 70-90° C., specifically 70° C., 75° C., 80° C., 90° C. After the raw materials are mixed, the heat preservation reaction time is preferably 2-5 hours, specifically 2 hours, 3 hours, 4 hours, 5 hours; until the NCO% is less than 0.05%, the reaction is completed.

[0092] In the present invention, step d) specifically includes: when the reaction in step c) is to the point where the NCO% is close to the theoretical value, the temperature is raised and the acrylate monomer is dripped into the system, and after the dripping is completed, the system is kept warm for reaction, thereby obtaining a thermal transfer adhesive resin. The target temperature for the temperature increase is the reaction temperature of 70 to 90°C mentioned above. The time for dripping the acrylate monomer is preferably 0.5 to 2 hours, and can be specifically 0.5 hours, 1 hour, 1.5 hours, or 2 hours. After the acrylate monomer is dripped, the system is kept warm for reaction, and the temperature and the time for the heat preservation reaction are the same as those described above. The reaction is terminated until the NCO% is less than 0.05%, and a transfer adhesive resin is obtained.

[0093] The present invention also provides a transfer adhesive resin prepared by the preparation method described in the above technical solution, which is a UV transfer adhesive resin.

[0094] The preparation method provided by the present invention first prepares two different polyester polyols E1 and E2 respectively, controls the molecular weights of the two polyester polyols, and then reacts the two polyester polyols with isocyanate and acrylate monomers. During the process, the ratio of the two polyester polyols and the ratio between the two polyester polyols and other reactants and the reaction conditions are controlled to obtain an oligomer resin that can be used for transfer adhesives. The toughness and wear resistance of the resin can be effectively improved to meet the special needs of the transfer adhesive market.

[0095] The present invention also provides a UV transfer adhesive, comprising the following components in mass ratio:

[0096]

[0097]

[0098] Wherein, the resin oligomer is the transfer adhesive resin described in the above technical solution.

[0099] Among them, the amount of the resin oligomer can be specifically 50%, 55%, 60%, 65%, 70%. The amount of the isobornyl acrylate (IBOA) can be specifically 10%, 15%, 20%, 25%, 30%. The amount of the hexanediol diacrylate (HDDA) can be specifically 10%, 15%, 20%. The amount of the photoinitiator TPO can be specifically 1 part, 1.5 parts, 2 parts. The amount of the photoinitiator 184 can be specifically 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts.

[0100] In the present invention, the UV transfer adhesive can be prepared by the following preparation method: resin oligomer, isobornyl acrylate (IBOA), hexanediol diacrylate (HDDA), photoinitiator TPO and photoinitiator 184 are uniformly mixed to obtain UV transfer adhesive.

[0101] The test results show that the transfer adhesive resin obtained by the present invention can make the curing energy of the transfer adhesive be 800w / cm 2 Below, wear resistance RCA>500 times, hardness above F, bending resistance value above 3mm, showing excellent curing speed, wear resistance and toughness.

[0102] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0103] Example 1

[0104] a) Preparation of polyester polyol E1 with a molecular weight of 800:

[0105] At room temperature, 40 parts of dimer acid, 30 parts of 3-methyl-1,5-pentanediol, 30 parts of 1,4-cyclohexanedimethanol and 0.3 parts of tetrabutyl titanate as catalyst are added to a reactor, high-purity nitrogen is introduced, the temperature is slowly raised to 200°C, and the reaction is carried out for 10 hours. Then, the water output and the acid value are recorded. When the acid value is less than 10 mgKOH / g, the remaining water is removed by vacuum until the acid value is less than 1 mgKOH / g. The reaction is completed to obtain saturated polyester polyol E1.

[0106] b) Preparation of polyester polyol E2 with a molecular weight of 500:

[0107] At room temperature, 60 parts of caprolactone monomer, 20 parts of 1,4-butanediol, 20 parts of 1,4-cyclohexanedimethanol and 0.5 parts of phosphoric acid catalyst were added to a reactor, high-purity nitrogen was introduced, the temperature was slowly raised to 120°C, and the reaction was carried out for 8 hours to obtain polyester polyol E2.

[0108] c) At room temperature, the materials were added into the reactor and reacted at 45° C. for 3 hours. When the NCO% was close to the theoretical value, an intermediate reactant was obtained and the next step of reaction was carried out.

[0109] The materials include:

[0110]

[0111] d) Raise the temperature to 80° C., add 50 parts of pentaerythritol triacrylate dropwise, and add for 1.5 hours. Keep the temperature at 80° C. for 2 hours. When the NCO% is less than 0.05%, the reaction is complete to obtain a transfer adhesive resin.

[0112] Example 2

[0113] a) Preparation of polyester polyol E1 with a molecular weight of 1000:

[0114] At room temperature, 25 parts of adipic acid, 20 parts of 1,4-cyclohexanedimethanol, 55 parts of 3-methyl-1,5-pentanediol and 0.5 parts of tetrabutyl titanate as catalyst are added to a reactor, high-purity nitrogen is introduced, the temperature is slowly raised to 210°C, and the reaction is carried out for 10 hours. Then, the water output and the acid value are recorded. When the acid value is less than 10 mgKOH / g, the remaining water is removed by vacuum until the acid value is less than 1 mgKOH / g. The reaction is completed to obtain saturated polyester polyol E1.

[0115] b) Preparation of polyester polyol E2 with a molecular weight of 800:

[0116] At room temperature, 65 parts of caprolactone monomer, 15 parts of 1,6-hexanediol, 10 parts of 1,4-cyclohexanedimethanol and 0.5 parts of phosphoric acid catalyst were added to a reactor, high-purity nitrogen was introduced, the temperature was slowly raised to 130°C, and the reaction was carried out for 6 hours to obtain polyester polyol E2.

[0117] c) At room temperature, the materials were added into the reactor and reacted at 50° C. for 3 hours. When the NCO% was close to the theoretical value, an intermediate reactant was obtained and the next step of reaction was carried out.

[0118] The materials include:

[0119]

[0120] d) Raise the temperature to 80° C., add 50 parts of pentaerythritol triacrylate dropwise, and add for 1.5 hours. Keep the temperature at 80° C. for 2 hours. When the NCO% is less than 0.05%, the reaction is complete to obtain a transfer adhesive resin.

[0121] Example 3

[0122] a) Preparation of polyester polyol E1 with a molecular weight of 1200:

[0123] At room temperature, 20 parts of dimer acid, 25 parts of methylhexahydrophthalic anhydride, 55 parts of 2,4-diethyl-1,5-pentanediol and 0.4 parts of tetrabutyl titanate catalyst were added to a reactor, high-purity nitrogen was introduced, the temperature was slowly raised to 230°C, and the reaction was carried out for 10 hours. Then, the water output and the acid value were recorded. When the acid value was less than 10 mgKOH / g, the remaining water was removed by vacuum until the acid value was less than 1 mgKOH / g. The reaction was completed to obtain saturated polyester polyol E1.

[0124] b) Preparation of polyester polyol E2 with a molecular weight of 600:

[0125] At room temperature, 65 parts of caprolactone monomer, 35 parts of 1,4-cyclohexanedimethanol and 0.5 parts of phosphoric acid catalyst were added to a reactor, high-purity nitrogen was introduced, the temperature was slowly raised to 110° C., and the reaction was carried out for 10 hours to obtain polyester polyol E2.

[0126] c) At room temperature, the materials were added into the reactor and reacted at 48° C. for 3 hours. When the NCO% was close to the theoretical value, an intermediate reactant was obtained and the next step of reaction was carried out.

[0127] The materials include:

[0128]

[0129] d) Raise the temperature to 80° C., add 55 parts of dipentaerythritol pentaacrylate dropwise, and add for 2 hours. Keep the temperature at 80° C. for another 2 hours. When the NCO% is less than 0.05%, the reaction is complete to obtain a transfer adhesive resin.

[0130] Example 4: Product performance test

[0131] 1. Prepare UV transfer adhesive

[0132] 1.1. Raw material composition see Table 1:

[0133] Table 1: Raw material composition of each transfer adhesive sample (1# to 7#)

[0134]

[0135] 2. Performance Testing

[0136] ⅰ. Curing energy: Apply the transfer adhesive on the substrate and cure it with an electrodeless mercury lamp to test the curing energy of the adhesive. The higher the required curing energy, the lower the curing speed.

[0137] ⅱ. Wear resistance RCA (number): Tested in accordance with standard GB / T1768-2006. The higher the number, the better the wear resistance.

[0138] ⅲ. Pencil hardness: Apply the transfer adhesive on the substrate and cure it with an electrodeless mercury lamp. The thickness of the adhesive layer is 2mm. After curing for 3 minutes, test the hardness of the paint film. The hardness level is divided into: H for hard, F for hardness between H and HB, HB for medium hardness, and B for soft. The hardness is H>F>HB>B.

[0139] ⅳ. Bending resistance (180°, mm): Apply the transfer glue on the tinplate in different thicknesses, and test whether the film breaks on a 180° bending instrument. The larger the value, the better the bending resistance.

[0140] The test results are shown in Table 2:

[0141] Table 2: Performance of each transfer adhesive sample (1#~7#)

[0142] 1# 2# 3# 4# 5# 6# <![CDATA[Curing energy (w / cm 2 )]]> 800 750 850 650 780 750 Wear-resistant RCA (number of times) >500 >500 >500 >500 >500 >500 Pencil hardness H H~F H H~F H F Bending resistance (180°, mm) 3 3.5 3 4 3.5 4

[0143] It can be seen from the test results in Table 2 that the transfer adhesive resin obtained by the present invention makes the curing energy of the transfer adhesive in the range of 800w / cm 2 Below, wear resistance RCA>500 times, hardness above F, bending resistance value above 3mm, showing excellent curing speed, wear resistance and bending toughness.

[0144] Comparative Example 1

[0145] The process was carried out in accordance with Example 1, except that 1,4-cyclohexanedimethanol was not added in step b).

[0146] Comparative Example 2

[0147] The method is implemented according to Example 1, except that in step b), the caprolactone monomer is replaced by adipic acid.

[0148] Comparative Example 3

[0149] The process was carried out in accordance with Example 1, except that pentaerythritol triacrylate was not added in step d).

[0150] Product testing:

[0151] A transfer adhesive was prepared according to the composition of the 1# transfer adhesive sample in Example 4, except that the resin in Example 1 was replaced by the resin in Comparative Example 1, the resin in Comparative Example 2, and the resin in Comparative Example 3, respectively. The obtained transfer adhesive samples were recorded as d1, d2, and d3, respectively.

[0152] According to the test method in Example 4, various performance tests were performed on samples d1, d2, and d3, and the results are shown in Table 3.

[0153] Table 3: Properties of samples d1-d3

[0154] d1 d2 d3 <![CDATA[Curing energy (w / cm 2 )]]> 950 750 830 Wear-resistant RCA (number of times) 350 420 395 Pencil hardness B B F Bending resistance (180°, mm) 2.5 3 3

[0155] It can be seen from the test results in Table 3 that compared with samples 1# to 7# in Table 2, the comprehensive performance of samples d1-d3 is worse, which proves that the present invention introduces cyclic alcohol monomers and caprolactone monomers in step b) to form a specific polyester polyol E2, and introduces acrylate monomers in step d) to react, so as to effectively improve the wear resistance and toughness of the material.

[0156] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a transfer adhesive resin, characterized in that: The following steps are involved: a) mixing an alcohol monomer, a dibasic acid substance and an esterification catalyst to react to obtain a saturated polyester polyol E1; The dibasic acid substance is at least one of a dibasic acid and a dibasic acid anhydride; b) mixing an alcohol monomer, a caprolactone monomer and a ring-opening catalyst to react to obtain a polyester polyol E2; The alcohol monomer comprises a cyclic alcohol monomer; the alcohol monomer is at least one of 1,4-cyclohexanedimethanol, 1,4-butanediol, 1,5-pentanediol and 1,6-hexanediol, and contains 1,4-cyclohexanedimethanol; c) mixing and reacting the materials to obtain an intermediate reactant; The material comprises the following components in parts by weight: Saturated polyester polyol E1 10-20 parts; Polyester polyol E2 15-30 parts; 10-20 parts of isocyanate; Catalyst 0.1~1 part; Inhibitor 0.1~1 part; d) mixing the intermediate reactant with an acrylate monomer to obtain a transfer adhesive resin; The acrylate monomer is at least one of pentaerythritol diacrylate, pentaerythritol triacrylate and dipentaerythritol pentaacrylate; There is no order restriction for step a) and step b).

2. The preparation method according to claim 1, characterized in that: In step a), the dibasic acid substance is at least one of adipic acid, succinic acid, phthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and 1,4-cyclohexanedicarboxylic acid.

3. The preparation method according to claim 1, characterized in that: In step a), the alcohol monomer is at least one of 1,4-cyclohexanedimethanol, methylpropanediol, 3-methyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, trimethylolpropane and pentaerythritol.

4. The preparation method according to claim 1, characterized in that: In step a), the reaction temperature is 180-230°C.

5. The preparation method according to claim 1, characterized in that: In step b), the reaction temperature is 110-130°C.

6. The preparation method according to claim 1, characterized in that: In step c), the reaction temperature is 40-60°C; In step d), the reaction temperature is 70-90°C.

7. The preparation method according to claim 1, characterized in that: In step a), the amount of each material is: 40-65 parts by weight of alcohol monomer; 30-50 parts by weight of dibasic acid; 0.1~1 parts by weight of esterification catalyst; In step b), the amount of each material is: 20-40 parts by weight of alcohol monomer; 30-65 parts by weight of caprolactone monomer; 0.1~1 parts by mass of ring-opening catalyst; In step c): The isocyanate is at least one of TMDI, hydrogenated MDI, IPDI and XDI; The catalyst is an organic bismuth catalyst; The polymerization inhibitor is at least one of p-hydroxyanisole, hydroquinone and 2,6-di-tert-butylphenol.

8. A transfer adhesive resin obtained by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Adhesive used for PP base material heat transfer film and preparation method thereof

    CN107779158A

  • Thermocurable and photocurable resin as well as preparation method and application thereof

    CN112358576A